From Screen to Society: How Popular Culture Shapes Values and Beliefs in Indonesian Teenagers - Hasan, Zainol; Syarifuddin, Syarifuddin; Mokodenseho, Sabil; Aziz, Adit Mohammad; Utami, Eva Yuniarti (West Science Social and Humanities Studies, 2023)
This research delves into the complex interplay between popular culture and the values and beliefs of Indonesian teenagers, offering insights into the multifaceted influence of media consumption. In an age marked by the ubiquity of globalized media, Indonesian adolescents are navigating a landscape where traditional cultural norms intersect with the allure of popular culture from around the world. Employing a mixed-methods approach, this study combines surveys, interviews, and content analysis to investigate how various forms of popular culture, including television, social media, music, and film, impact the attitudes, values, and beliefs of Indonesian teenagers. The research also explores themes, messages, and the negotiation of these influences within the context of cultural identity. Findings reveal that popular culture undeniably shapes the perceptions and beliefs of Indonesian youth, but it also reflects their agency in adapting and reaffirming their cultural identity amidst the dynamic forces of globalization.